Global Trends in Telemedicine Design Approaches Over the Past Decade: Tren Global dalam Pendekatan Desain Telemedisin Selama Sepuluh Tahun Terakhir - Zulfikar, Aditya Rahmat; Arini, Merita (Indonesian Journal of Innovation Studies, 2025)
General Background: Telemedicine has rapidly evolved as a pivotal component of global healthcare, providing remote services that enhance clinical outcomes and patient access. Specific Background: Despite significant technological advancements, the design dimension of telemedicine systems remains crucial for ensuring usability, inclusivity, and sustainability. Knowledge Gap: Previous studies have primarily addressed isolated aspects of interface or AI integration, lacking a comprehensive, data-driven mapping of global design trends in telemedicine. Aims: This study employs a bibliometric analysis of 1,115 open-access Scopus-indexed publications (2014–2024) to map thematic clusters, identify evolving research focuses, and evaluate key design approaches in telemedicine. Results: Findings reveal a sharp rise in publications post-2020 driven by the COVID-19 pandemic, with six major clusters encompassing user-centered design, clinical effectiveness, access equity, research methodology, pandemic response, and integration of scientific databases. Novelty: By synthesizing technological, clinical, and socio-economic perspectives, this research provides the first decade-long, global bibliometric analysis of telemedicine design, highlighting adaptive user-centered and evidence-based approaches. Implications: The results underscore the necessity for inclusive, crisis-responsive, and evidence-informed design strategies to enhance telemedicine’s scalability and equity across diverse healthcare contexts Highlights: Highlights rapid growth of telemedicine design research, especially post-COVID-19. Identifies six global thematic clusters guiding inclusive and adaptive system design. Emphasizes user-centered, evidence-based approaches for sustainable telehealth solutions. Keywords: Telemedicine, Design, User Centered, Bibliometric, Healthcare